Exploring the surgical landscape of pancreatic neuroendocrine neoplasia in Austria: Results from the ASSO pNEN study group. Issue 2 (February 2019) - Primavesi, Florian; Klieser, Eckhard; Cardini, Benno; Marsoner, Katharina; Fröschl, Uwe; Thalhammer, Sabine; Fischer, Ines; Hauer, Andreas; Urbas, Romana; Kiesslich, Tobias; Neureiter, Daniel; Zitt, Matthias; et al.
Abstract: Introduction: Pancreatic neuroendocrine neoplasia (pNEN) show increasing incidence and management is complex due to biological heterogeneity. Most publications report isolated high-volume single-centre data. This Austrian multi-centre study on surgical management of pNENs provides a comprehensive real-life picture of quality indicators, recurrence-patterns, survival factors and systemic treatments. Methods: Retrospective, national cohort-study from 7 medium-/high-volume centres in Austria, coordinated under the auspices of the Austrian Society of Surgical Oncology (ASSO). Results: Two-hundred patients underwent resection for pNEN, 177 had non-functioning tumours and 31 showed stage 4 disease. Participating centres were responsible for 2/3 of pNEN resections in Austria within the last years. The mean rate of completeness of variables was 98.6%. Ninety-days mortality was 3.5%, overall rate of complications was 42.5%. Morbidity did not influence long-term survival. The 5-year overall-survival (OS) was 81.3%, 10-year-OS 52.5% and 5-year recurrence-free-survival (RFS) 69.8%. Recurrence was most common in the liver (68.1%). Four out of five patients with recurrence underwent further treatment, most commonly with medical therapy or chemotherapy. Multivariable analysis revealed grading (HR:2.7) and metastasis (HR:2.5) as significant factors for relapse. Tumours-size ≥2 cm (HR:5.9), age ≥60 years (HR:3.1), metastasis (HR:2.3) and grading (HR:2.0) were associated with OS. Tumours <2 cm showed 93.9% 10-year-OS, but 33% had G2/G3 grading, 12.5% positive lymph-nodes and 4.7% metastasis at diagnosis, each associated with significant worse survival. Conclusion: Resection of pNENs in Austria is performed with internationally comparable safety. Analysed factors allow for risk-stratification in clinical treatment and future prospective trials. A watch-and-wait strategy purely based on tumour-size cannot be recommended.